2023
DOI: 10.3390/membranes13030334
|View full text |Cite
|
Sign up to set email alerts
|

New Insights into the Fouling of a Membrane during the Ultrafiltration of Complex Organic–Inorganic Feed Water

Abstract: This paper presents an analysis of the fouling of a ceramic membrane by a mixture containing high concentrations of humic acid and colloidal silica during cross-flow ultrafiltration under various operating conditions. Two types of feed water were tested: feed water containing humic acid and feed water containing a mixture of humic acid and colloidal silica. The colloidal silica exacerbated the fouling, yielding lower fluxes (109–394 L m−2 h−1) compared to the humic acid feed water (205–850 L m−2 h−1), while th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 28 publications
2
1
0
Order By: Relevance
“…These results align with the conclusions of studies by researchers such as Ridgway et al and other works referenced in [ 47 , 48 , 49 , 50 , 51 , 52 ], which demonstrated that modifications in membrane surface roughness can significantly impact fouling behavior and surface energy calculations. Ridgway’s study on bacterial adhesion highlighted the critical role of surface roughness in biofilm formation, emphasizing that hydrophobic interactions between bacterial cell surface components and the membrane surface are crucial during the initial stages of adhesion and biofilm development.…”
Section: Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…These results align with the conclusions of studies by researchers such as Ridgway et al and other works referenced in [ 47 , 48 , 49 , 50 , 51 , 52 ], which demonstrated that modifications in membrane surface roughness can significantly impact fouling behavior and surface energy calculations. Ridgway’s study on bacterial adhesion highlighted the critical role of surface roughness in biofilm formation, emphasizing that hydrophobic interactions between bacterial cell surface components and the membrane surface are crucial during the initial stages of adhesion and biofilm development.…”
Section: Resultssupporting
confidence: 91%
“…These results align with the conclusions of studies by researchers such as Ridgway et al and other works referenced in [47][48][49][50][51][52], which demonstrated that modifications in membrane surface roughness can significantly impact fouling behavior and surface energy calculations. Ridgway's study on bacterial adhesion highlighted the critical role of surface The results of morphological studies (AFM) and contact angle trends demonstrated that the membrane's surface roughness and texture have a significant impact on its wettability and surface energy characteristics.…”
Section: Wettability and Surface Free Energysupporting
confidence: 91%
See 1 more Smart Citation